Influence of rock mass rating and in situ stress on stability of roof rock in bord and pillar development panels. (2015) - Sinha, R.K.; Jawed, M; Sengupta, S
The re-orientation of bord and pillar layout is dictated by the direction of the horizontal stress. However, the competence of strata expressed in terms of rock mass rating (RMR) and the magnitude of in situ stress have a persuasive influence in deciding the gain out of re-orientation of galleries. However, a few queries like: a) "Is it essential to re-orient all bord and pillar workings vis-à-vis the direction of in situ stress?"; b) "What if the strata are competent and the workings are subjected to low magnitude of horizontal stress?"; c) "What happens to a bord and pillar workings affected by high horizontal stress and having incompetent strata?" have remained unaddressed. This paper, therefore, addresses such queries through a new approach of classification of the bord and pillar development workings using numerical modelling. This classification system will aid field engineers in deciding the need for re-orienting galleries vis-à-vis the RMR and in situ stress.